SHAN, N.H., and BRYAN, W.W. (Eds.), 1976: Tropical pasture research. Principies and methods ("La investigación en pastos tropicales. Método y fundamentos"). CS.I.R.O. Bulletin 51, Commonwealth Bureau of Pastures and Field Crops. Hurley, Berkshire, England - Caballero, R. (Pastos, 2011)
SHAN, N.H., and BRYAN, W.W. (Eds.), 1976: Tropical pasture research. Principies and methods ("La investigación en pastos tropicales. Método y fundamentos"). CS.I.R.O. Bulletin 51, Commonwealth Bureau of Pastures and Field Crops. Hurley, Berkshire, England, pp. 454.